(untitled) (Journal of Atomic and Molecular Sciences, 2021)
The theoretical modified Khare (BEB) model has been used to calculate the total cross sections for L_1, L_2 and L_3-subshells ionization of gold atom due to electron and positron impact for projectile energy varying from the threshold of ionization to 60 times the threshold energy For L subshells the present cross section due to electron and positron impact cross sections are in remarkable agreement with available experimental data and other theoretical cross sections. Total L shell ionization cross sections have been also calculated in the energy varying from the threshold of ionization to several MeV by electron impact. It is found good agreement with available experimental data. The investigation for other atoms is in progress.